The Role of Health Consciousness and Trust on Gen Y and Gen Z Intention to Purchase Functional Beverages - Firya Fadhila Fathin; Adila Sosianika; Fatya Alty Amalia; Rafiati Kania (Journal of Consumer Sciences, 2023)
This study explored the purchasing intentions of Generation Y and Generation Z concerning functional beverages, with a focus on health awareness and trust as key influencing factors. This research aims to investigate the determinant factors of the consumption of functional beverages as an alternative to sugary drinks among Generation Y and Z in Indonesia. The study population comprises individuals aged 18 to 40, with a particular focus on Generation Y (born 1981-1996) and Generation Z (born 1997-2012) in the West Java Region. Purposive sampling was carried out to select 406 participants. Primary data were collected through a Google Form-hosted online questionnaire, focusing on respondents' characteristics, purchasing habits, health consciousness, and intentions to purchase functional beverages. SmartPLS 3.0 was employed to analyze the data. Various analyses, including descriptive, measurement, Fornell-Larcker, structural model, and path analyses, were carried out. The results indicated noteworthy connections between health consciousness, trust, and purchase intention. Respondents, primarily from Generation Z, exhibited a positive inclination towards health consciousness and trust, suggesting a promising opportunity for the functional beverage industry.